Developing, Implementing, and Evaluating a Professional Practice Model. (January 2015) - Basol, Roberta; Hilleren-Listerud, Amy; Chmielewski, Linda
<x xml:space="preserve">Abstract</x> This article describes how The Compass, a professional practice model (PPM), was developed through clinical nurse involvement, review of literature, expert opinion, and an innovative schematic. Implementation was supported through a dynamic video account of a patient story, interwoven with The Compass. Postproject evaluation of PPM integration demonstrates opportunities for professional nursing development and future planning.